Development of non-traditional renewable energy sources in Russia: prospects and problems - A. S. Flaksman (Вестник университета, 2022)
The article considers one of the main trends of the industrial revolution 4.0, namely the decarbonization trend, including through the development of renewable energy sources. A significant lag in the development and implementation of renewable energy sources in the Russian Federation compared to the countries of the European Union has been revealed. An analysis of the main reasons for this situation showed the insufficient development of appropriate state mechanisms for stimulating alternative energy sources in Russia, as well as the country’s sufficient supply of hydrocarbon fuel. Since solar and wind generation account for the largest share in the structure of renewable energy sources, the author studied existing and promising technologies in the field of solar and wind energy. The advantages and disadvantages of using renewable energy sources are analyzed. The article describes the main mechanisms of state support aimed at the prospective development of renewable energy in Russia.